Association of childhood health with adulthood chronic kidney disease: results from the China Health and Retirement Longitudinal Study - Lian, Rong; Wang, Zheng-he (Frontiers in Public Health, 2025)
ObjectiveAdverse Childhood Experiences have been well-documented as a risk factor for chronic kidney disease (CKD) in adulthood. However, the link between childhood health and adulthood CKD risk is still unclear. This study aimed to explore the connection between childhood health and the likelihood of developing CKD in adulthood.MethodsParticipants were drawn from the third wave of the China Health and Retirement Longitudinal Study (CHARLS). The CKD was identified based on the estimated Glomerular Filtration Rate (eGFR) and self-reported doctor-diagnosed kidney disease. Childhood health status was assessed through a standard questionnaire and categorized into excellent, fair, and poor groups.ResultsThe prevalence of CKD was 11.7% (1,480 out of 12,609). The eGFR levels in the self-reported Fair and Poor groups were significantly lower than those in the Excellent group (p < 0.05). Compared to the Excellent group, individuals in the Poor group reported a higher risk of CKD (OR = 1.38; 95% CI: 1.12–1.70; p = 0.002), even after adjusting for factors such as age, sex, smoking, alcohol consumption, physical activity, highest education level, use of Chinese traditional medicine, diabetes, hypertension, BMI, marital status, and annual household income (OR = 1.24; 95% CI: 1.01–1.54; p = 0.047).ConclusionThe CKD prevalence is notably high in the Chinese adults aged more than 45 years, and a history of poor health in childhood may significantly contribute to the risk of CKD in later life.